Polarization-insensitive wavefront shaping using the Pancharatnam–Berry phase - Jisha, Chandroth P.; Nolte, Stefan; Alberucci, Alessandro (Optics Letters, 2019)
We discuss a method to achieve a polarization-independent modulation of the electromagnetic wavefront based upon the Pancharatnam–Berry phase. When the length of the twisted anisotropic material is equal to the birefringence length (i.e., full-wave plate length), a phase delay proportional to the squared transverse derivative of the twisting angle appears. Physically, the phase delay is associated with the Kapitza effect applied to the Pancharatnam–Berry phase. Our theoretical results are confirmed by finite-difference time-domain (FDTD)-based numerical simulations.
CRIS-Team Scopus Importer:2023-04-20